2001
DOI: 10.1080/gye.15.3.170.177
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual irregularity in the first postmenarchal years: an early clinical sign of polycystic ovary syndrome in adolescence

Abstract: We determined the hormonal, metabolic and ultrasonographic pattern of adolescents with menstrual irregularity since menarche but without clinical signs of hyperandrogenism with the aim of evaluating whether this condition represents an early stage of polycystic ovary syndrome (PCOS). These adolescents were divided in two groups: 13 adolescents with irregular cycles (IC) within the first 3 postmenarchal years (IC < or = 3) and 15 adolescents having persistent irregular cycles for more than three postmenarchal y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 21 publications
3
19
0
2
Order By: Relevance
“…Menstrual irregularity is a common feature of PCOS, occurring in more than 75% of the adult PCOS population, and is often the earliest clinical manifestation in the adolescent [103,104]. van Hooff and colleagues observed polycystic ovaries in 9% of adolescent girls with regular menstrual cycles, in 28% with irregular cycles (average cycle length between 22 and 41 days), and in 45% with oligomenorrhea and found a similar association with higher androgen levels.…”
Section: Adolescencementioning
confidence: 82%
“…Menstrual irregularity is a common feature of PCOS, occurring in more than 75% of the adult PCOS population, and is often the earliest clinical manifestation in the adolescent [103,104]. van Hooff and colleagues observed polycystic ovaries in 9% of adolescent girls with regular menstrual cycles, in 28% with irregular cycles (average cycle length between 22 and 41 days), and in 45% with oligomenorrhea and found a similar association with higher androgen levels.…”
Section: Adolescencementioning
confidence: 82%
“…7 Various literature shows that the levels of free testosterone, LH, and the LH/FSH ratio in adolescents with menstrual irregularity with no clinical signs of hyperandrogenism are similar to those of patients with PCOS and higher than those of adolescents with regular menstrual cycles. 3,7,18,28 In present study, we found significantly higher LH levels (p value<0.5), but not FSH levels (p value 0.4) in adolescent presenting with menstrual irregularities i.e.13 of 18 adolescents who met the Rotterdam criteria of PCOS had raised LH levels. The mean testosterone and DHEA-S levels in adolescents with menstrual irregularity were significantly higher than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…7 In our study we calculated the fasting and postprandial glucose levels, none of the adolescents, either cases or controls, had abnormal values, probably because the elevation in the glucose levels begins only when (even with high serum insulin levels) the receptor resistance is such that the glucose levels cannot be controlled; in this stage the patient may present glucose intolerance, a step that leads to type II diabetes later on. This study confirms the previous findings that labetalol is an effective and safe drug for use in the control of blood pressure in pregnancy-induced hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know that it is very common for girls to have irregular periods immediately after achieving menarche. Hypothalamic pituitary ovarian axis takes time to mature [1]. This endocrine function matures progressively over a period of many months and sometimes it may take one or two years to regularize after menarche.…”
Section: Features Of Pcosmentioning
confidence: 99%